Diversidade de metazoários (parasitos) em Gonatodes humeralis (Squamata, Sphaerodactylidae) em matas de galeria da Ilha do Maranhão, Brasil - LIMA, Hugo Nunes Gomes (2014)
The knowledge of the aspects of parasitism on the neotropical lizards has grown in recent decades, but despite the great diversity of lizards, there are still few work related to parasites for this group. Studies on lizards in forest aspects of composition, diversity, abundance, behavior, ecology, biogeography, genetics, reproductive biology, responses to anthropic disturbances and habitat use. The present work has the proposal to investigate the parasite- and to evaluate the influence of the process of anthropization of gallery in this relationship. Specifically, we tested the null hypotheses of absence of relationship between sex and size of the lizard Gonatodes humeralis with the parasitic, and absence of relationship between environmental degradation and the parasitic rate in the lizards. The work was carried out in the island of Maranhão (2 ° 45'S 44 ° 20'S and 2 ° 25'S 44 ° 01'O), northeast of Brazil, in 10 fragments of gallery forests. Twenty lizards located by the active visual search method were captured manually in the rainy season, and 20 in the dry season, in each gallery forest. The lizards were to the laboratories, where they were anesthetized, sacrificed, sexed and measured with a digital caliper. Afterwards, the intensity of external parasites and internally in the body of each lizard. To assess the level of local degradation were 50 sampling points along the stream of each gallery forest, where the types of impacts observed, such as the presence of organic waste or inorganic, faeces, sewage, deforestation and others. The 277 parasites found infested only 103 (25.7%) lizards of the 400 collected. Whereas ecto endoparasites, 121 infested 52 (25.2%) of the 206 females, and 156 infested 51 (26.1%) of 195 males. In all 10 forest fragments, there were eight genera of parasites, Eutrombicula (3.5%), Amblyoma (0.2%), Physalopteroid (1.7%), Physaloptera (15.7%), Hirstiella (0.2%), Skrzabellellia (0.5%), Camallanus (0.5%), Parapharyngodon (5.2%), as well as the classes cestoda (1,5%) and trematoda (0,5%). There was no significant relationship between the size or gender of G. humeralis with the parasitic infection. There was also no significant relationship between the level of degradation of and the parasitic rate. However, one of the forests, already very narrow due to the deforestation and in close contact with a densely populated region, which causes contamination of the stream with sewage, was the one that presented one of the highest parasite rates. The low prevalence and richness of parasite infection in G. humeralis have also been observed in other studies that focused on the helmintofauna in Geckonids. The arboreal habit, the general diet, the low handling and the "sit-in" foraging mode of G. humeralis may explain the composition of helmintofauna, composed of monoxenic and common life.